The Cancer/Testis Antigen Gene VCX2 Is Rarely Expressed in Malignancies but Can Be Epigenetically Activated Using DNA Methyltransferase and Histone Deacetylase Inhibitors - Jakobsen, Mie K.; Traynor, Sofie; Stæhr, Mette; Duijf, Pascal G.; Nielsen, Aaraby Y.; Terp, Mikkel G.; Pedersen, Christina B.; Guldberg, Per; Ditzel, Henrik J.; Gjerstorff, Morten F. (Frontiers in Oncology, 2021)
Identification of novel tumor-specific targets is important for the future development of immunotherapeutic strategies using genetically engineered T cells or vaccines. In this study, we characterized the expression of VCX2, a member of the VCX/Y cancer/testis antigen family, in a large panel of normal tissues and tumors from multiple cancer types using immunohistochemical staining and RNA expression data. In normal tissues, VCX2 was detected in the germ cells of the testis at all stages of maturation but not in any somatic tissues. Among malignancies, VCX2 was only found in tumors of a small subset of melanoma patients and thus rarely expressed compared to other cancer/testis antigens such as GAGE and MAGE-A. The expression of VCX2 correlated with that of other VCX/Y genes. Importantly, we found that expression of VCX2 was inversely correlated with promoter methylation and could be activated by treatment with a DNA methyltransferase inhibitor in multiple breast cancer and melanoma cell lines and a breast cancer patient-derived xenograft. The effect could be further potentiated by combining the DNA methyltransferase inhibitor with a histone deacetylase inhibitor. Our results show that the expression of VCX2 can be epigenetically induced in cancers cells and therefore could be an attractive target for immunotherapy of cancer.